SOME ISSUES OF GOVERNANCE OF JOINT STOCK COMPANIES - Khachikyan, Martin (State and Law, 2022)
The subject of discussion in the article is the practical tasks identified as a result of a systematic study and analysis of the ordinary activities of the general meeting - the highest body of corporate governance in the Republic of Armenia, as well as proposals aimed at solving existing problems. In particular, the practical problems that arose as a result of the failure to hold the annual meeting within the specified period were presented, and the need to introduce legislative changes aimed at solving them was justified.